Analysis of anthropometric characteristics and jumping ability in junior top level volleyball athletes. Comparison by role - Ciccarone, G.; Fontani, G.; Albert, A.; Zhang, L.; Cloes, M. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Results pointed out that in junior top level volleyball, the anthropometrical profile of the players is directly related to specific variables which must be used to select talented athletes and to plan training in connection with specific role of the player in the game. Because of the reduced duration of the game episodes and to the increasing intensity of the game rhythm, the modern volleyball involve increasingly the alactacid anaerobe component. It is for all above reasons that top level volleyball needs always more muscular powerful athletes who are also fast and able to use high jumping abilities. For that reason, assessment, training and follow up of the jumping abilities become some of the most determinant aspects of the player's effectiveness. Data underline the interest of the use of specific tests to identify the jumping ability of volleyball athletes. The protocole developed in that study can provide determinant information during the first phase of athletes' selection.